A comparison of the Refrigerated Adsorption Drying of Daucus carota with fluidized bed drying. (15th January 2022) - Nandhu Lal, A.M.; Krishnamurthy, Sriram; Girinandagopal, M.S.; Kothakota, Anjineyulu; kumar, Raj; Venugopalan, V.V.; Padma Ishwarya, S; Venkatesh, T.
Abstract: The present study aims at establishing the resourcefulness of a low-temperature/low-humidity dryer, namely, Refrigeration Adsorption Dehumidified Dryer (RADD) for the drying of carrots, vis-à-vis a fluidized bed dryer (FBD). Notably the RADD is a customized design developed by the Agro-Processing and Technology Division of CSIR-NIIST, India. The differently dried carrot samples were compared for the drying rate, rehydration ratio, shrinkage kinetics and physicochemical quality characteristics such as moisture content, morphology, color and sensory attributes. The moisture content of carrot was reduced from an initial value of 80 g moisture/100 g of sample to 10 g moisture/100 g of sample (wet basis). Though the drying rate was higher in FBD than RADD, the percentage removal of moisture content was higher in the latter due to the synergistic effect of heating and dehumidification of drying air. Similarly, rehydration of RADD-dried carrots was slower (4 h) than their FBD counterparts (3 h). But, within the aforementioned duration, RADD-dried carrots achieved ∼96% of rehydration weight attained by the FBD-dried carrots. The total phenolic and flavonoid contents and amount of β-carotene retained in dried carrot samples were higher after RADD. The color parameters of dried samples were not significantly different between the two drying techniques. Graphical abstract: Image 1 Highlights: Performance comparison of Refrigerated Adsorption Dehumidified Drying (RADD) and Fluid Bed Drying (FBD) is done. Retention of bioactive compounds is high in RADD. Rehydration ratio and Drying rate is high in FBD. Colour and Textural attributes are better in RADD. RADD is found to be an interesting alternative for FBD for drying agro produces and heat sensitive materials.